The Institution Image and Trust and Their Effect on the Positive Word of Mouth - Harsono, Soni (Universitas Prasetiya Mulya, 2014)
In marketing, it is important to see how competitive a university is. Among public universities (PTN) and private universities (PTS), it shows a very competitive situation recently. To overcome this problem, it requires shaping up the institution image and trust for increasing the positive word of mouth among students. This study aims to determine the effect of the institution image, trust both partially and simultaneously on the positive word of mouth by the students of private universities in Surabaya with their accreditation levels of A, B and C. The sample consists of students from six colleges with accreditation ratings A, B, and C totaling 125 students. Accidental sampling technique was done using a sampling technique of multiple regression analysis with SPSS version 17. It shows, for the college with accreditation category C, the image of the institution both partially and simultaneously has significant positive effect on the positive word of mouth. For the college accreditation category B, the image of the institution and trust simultaneously has significant positive effect on the positive word of mouth and, finally, trust in accreditation category A has significant positive effect on the positive word of mouth and the institution image and trust simultaneously have significant positive effect on the positive word of mouth.